Odpowiedzi

2010-02-07T11:24:09+01:00
X(kwadrat) - 4+ y(kwadrat)+4= 16- x(kwadrat)+ y(kwadrat)
x (kwadrat)+y (kwadrat)+ x (kwadrat)- y (kwadrat)=16
2x (kwadrat)= 16 /: 2
x= 8 lub 8(kwadrat = 64 - nie jestem pewna





Najlepsza Odpowiedź!
2010-02-07T11:25:55+01:00
(x-2)² + (y+2)² = (4-x)² + y²
(x+1)² + (y-1)² = (x-5)² + (y-3)²


x²-4x+4 + y²+4y+4= 16-8x+x²+y²
x²+2x+1+y²-2y+1=x²-10x+25+y²-6y+9


x²-4x+y²+4y+8x-x²-y²=16-4-4
x²+2x+y²-2y-x²-10x-y²+6y=25+9+1+1

4x+4y=8/×2 =========> | 4x+4×52/11=8
-8x+3y=36 | 4x+ 208/11=8
| 4x= 8-208/11
8x+8y=16 | 4x= 88/11 - 208/11
-8x+3y=36 | 4x= -120/11 /× 1/4
| x= -30/11
11y=52/÷11 | x= 2 i 8/11
y= 52/11

x= 2 i 8/11
y= 52/11